2015
DOI: 10.1007/s10461-015-1050-x
|View full text |Cite
|
Sign up to set email alerts
|

Periconception HIV Risk Behavior Among Men and Women Reporting HIV-Serodiscordant Partners in KwaZulu-Natal, South Africa

Abstract: HIV-infected men and women who choose to conceive risk infecting their partners. To inform safer conception programs we surveyed HIV risk behavior prior to recent pregnancy amongst South African, HIV-infected women (209) and men (82) recruited from antenatal and antiretroviral clinics, respectively, and reporting an uninfected or unknown-HIV-serostatus pregnancy partner. All participants knew their HIV-positive serostatus prior to the referent pregnancy. Only 11% of women and 5% of men had planned the pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 82 publications
(84 reference statements)
0
25
1
Order By: Relevance
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Mmeje et al found that HIV-infected individuals experienced stigma from their communities and fear of vertical transmission, so do not discuss fertility intentions with their providers [54]. Other studies found that education and building awareness around SCS impacts uptake and acceptability of safer conception services in HIV-affected couples [25, 36, 46, 55, 56, 59, 60], but patients fear of judgment for wanting children remained a barrier to receiving SCS counseling and education [27, 46, 51, 54]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About one-third of the sample reported using TUI at any time during the study, which is more than the studies conducted in South Africa that found rates of 3% [30] and 17% [22], although our time frame was longer. The validity of self-reported data regarding TUI use is challenged by social desirability, but also the difficulty in assessing whether participants who report using the method, used it correctly.…”
Section: Discussionmentioning
confidence: 61%